Factors Influencing Foreign Products Purchase Intention of Mongolian Consumers - Gantulga, Urandelger; Ganbold, Munkhbayasgalan (Asia Marketing Journal (Online), 2022)
The current study examines how ethnocentrism influences the relationship between country image, product image, quality, and purchase intention for foreign goods. It is necessary to explore and analyze the connection between consumer ethnocentrism and purchase intention to develop marketing strategies that influence consumers' purchasing decisions. Accordingly, this article develops the research model to determine the impact of specific product determinants on consumer purchase intention towards foreign products. An online survey was carried out to reach the research objective. Four hundred effective questionnaires were analyzed using SPSS 23 and Smart PLS 3.3. The results showed that foreign product quality and image have a significant positive impact on consumers' intentions to buy foreign goods. Furthermore, consumer ethnocentrism significantly moderates product quality and purchase intention relationships. The study's findings could help marketers develop effective marketing techniques while also being helpful to academics and consumers in general.